Linguistic prehistory and identity in Nigeria’s Bini-Ife pre-eminence contestation - Lewis, Demola (Multilingual Margins: A journal of multilingualism from the periphery, 2018)
On the basis of genetic classification, Edoid (of the Bini people of Nigeria) is conceived as an offshoot of Benue-Congo earlier than Yoruboid (of the Ife people of Nigeria). However, the reverse is the case when viewed from the sociolinguistic platforms of population, prestige and power. Thus, in 2004, the Edoid patriarch of Bini launched a biography, wherein he narrated the Bini origin of the Ife monarchy. This sparked a barrage of unguarded responses from both sides of the controversy, largely centred on different interpretations to oral tradition. By exploring language as custodian of prehistory, this paper makes a linguistic contribution to the continuing debate about which predates the other between Ife (Yoruboid) and Bini (Edoid) of southwestern Nigeria. It pieces together evidence of cognate lexical simplification, patterns of cognate counting systems, sound inventory, and decadence of vowel harmony, which support the chronological pre-eminence of Edoid over Yoruboid; thus, calling for archaeological, anthropological and geographical inspection.